Integrating corporate responsbility into investor relations. Sustainability report as a part of investor relations. - Saloheimo, Hanna (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Corporate responsibility is a question that many stakeholders are interested in. These stakeholders can be e.g. company’s employees, partners, clients, media or investors. Especially for listed companies, investors are one of the most important stakeholders. It is essential for a company to maintain the trust of current investors and gain the trust of potential investors. Investors cannot be divided only into two groups, individual and institutional investors. Investors differ a lot, especially when it comes to investment decisions. Investors can make their investment decisions based on many things, and strong financial performance is not necessarily good enough a reason. Socially responsible investors value responsibility and sustainability related factors when making investment decisions. These things can be divided into three dimensions: environmental, social and economic responsibility. Many companies disclose a sustainability report in order to be able to answer to the needs of different stakeholders, including investors. The purpose of this thesis was to study how companies integrate corporate responsibility into investor relations, and how sustainability report can be used in investor relations. Furthermore, this thesis examined the key elements of sustainability reports. The research was made by a qualitative study in two phases. In the first phase five representatives of two Finnish listed companies, KONE and Kesko were interviewed. The interviewees are professionals within investor relations and corporate responsibility communications. In the second phase of the study the sustainability reports of these two companies were analyzed with content analysis. The existing theory and the interviews created the base for the content analysis. This study suggests that there is a connection between corporate responsibility and investor relations, and those should be integrated. Socially responsible investors are an important target group for companies, and companies should be able to respond to their and other stakeholders’ needs. Sustainability report can be used as a tool both within the company and in external communication for these purposes.

Yritysten yhteiskuntavastuu on kysymys, joka kiinnostaa yritysten monia eri sidosryhmiä, kuten työntekijöitä, yhteistyökumppaneita, asiakkaita, eri medioita ja sijoittajia. Etenkin julkisesti noteeratuissa yrityksissä sijoittajat ovat yksi tärkeimmistä kohderyhmistä. Yritysten on tärkeää ylläpitää nykyisten sekä ansaita potentiaalisten sijoittajien luottamus. Jako yksityisten ja institutionaalisten sijoittajien välille ei ole ainoa tapa erotella sijoittajia. Sijoittajat voivat tehdä sijoituspäätöksiään monin eri perustein, ja pelkkä taloudellinen menestys ei välttämättä riitä perusteeksi sijoittaa yritykseen. Vastuulliset tai eettiset sijoittajat (Socially Responsible Investors) huomioivat sijoituspäätöksissään yrityksen vastuullisuuteen liittyviä tekijöitä. Nämä tekijät voidaan karkeasti jakaa kolmeen ulottuvuuteen: ympäristövastuu, sosiaalinen vastuu ja taloudellinen vastuu. Vastatakseen sijoittajien tarpeisiin yritysten täytyy tuoda vastuullisuus osaksi yrityksen toimintaa sekä viestintää. Tämän tutkimuksen tarkoituksena oli tarkastella, miten yritykset voivat ottaa yhteiskuntavastuun osaksi sijoittajaviestintää, ja miten yhteiskuntavastuuraportti voi toimia yhtenä sijoittajaviestinnän keinona. Lisäksi kiinnostuksen kohteena olivat yhteiskuntavastuuraportin elementit. Tutkimus toteutettiin kvalitatiivisena tutkimuksena, joka jakautui kahteen vaiheeseen. Ensimmäisessä vaiheessa haastateltiin kahden suomalaisen pörssiyrityksen, KONEen ja Keskon edustajia. Nämä viisi haastateltavaa ovat sijoittajaviestinnän sekä yhteiskuntavastuuviestinnän ammattilaisia. Tutkimuksen toisessa vaiheessa näiden kahden yrityksen yhteiskuntavastuuraportit analysoitiin sisällönanalyysin kautta. Olemassa oleva teoria ja haastattelut loivat raamit sisällönanalyysille. Tämän tutkimuksen tulokset viittaavat siihen, että sijoittajaviestinnän ja yritysten yhteiskuntavastuun välillä on yhteys ja yhteiskuntavastuu tulisi tuoda osaksi sijoittajaviestintää. Vastuulliset sijoittajat ovat yritysten tärkeä kohderyhmä, ja yritysten tulee olla valmiita vastaamaan vastuullisten sijoittajien sekä muiden sidosryhmien tarpeisiin. Yhteiskuntavastuuraportti voi toimia työkaluna sekä yrityksen sisäisesti että ulkoisessa viestinnässä näihin tarkoituksiin.
Yrityksen yhteiskuntavastuu osana sijoittajaviestintää. Yhteiskuntavastuuraportti sijoittajaviestinnän keinona.